Distinct Conformational Dynamics of Three G Protein-Coupled Receptors Measured Using FlAsH-BRET Biosensors - Bourque, Kyla; Pétrin, Darlaine; Sleno, Rory; Devost, Dominic; Zhang, Alice; Hébert, Terence E. (Frontiers in Endocrinology, 2017)
A number of studies have profiled GPCR conformation using fluorescent biaresenical hairpin binders (FlAsH) as acceptors for BRET or FRET. These conformation-sensitive biosensors allow reporting of movements occurring on the intracellular surface of a receptor to investigate mechanisms of receptor activation and function. Here, we generated eight FlAsH BRET-based biosensors within the sequence of the β2-adrenergic receptor (β2AR) and compared agonist-induced responses to the angiotensin II receptor type I (AT1R) and the prostaglandin F2α receptor (FP). Although all three receptors had FlAsH binding sequences engineered into the third intracellular loops and carboxyl-terminal domain, both the magnitude and kinetics of the BRET responses to ligand were receptor-specific. Biosensors in ICL3 of both the AT1R and FP responded robustly when stimulated with their respective full agonists as opposed to the β2AR where responses in the third intracellular loop were weak and transient when engaged by isoproterenol. C-tail sensors responses were more robust in the β2AR and AT1R but not in FP. Even though GPCRs share the heptahelical topology and are expressed in the same cellular background, different receptors have unique conformational fingerprints.